2019
DOI: 10.3390/ijms20194794
|View full text |Cite
|
Sign up to set email alerts
|

Association with PD-L1 Expression and Clinicopathological Features in 1000 Lung Cancers: A Large Single-Institution Study of Surgically Resected Lung Cancers with a High Prevalence of EGFR Mutation

Abstract: Programmed cell death ligand 1 (PD-L1) expression is an important biomarker for predicting response to immunotherapy in clinical practice. Hence, identification and characterization of factors that predict high expression of PD-L1 in patients is critical. Various studies have reported the association of PD-L1 expression with driver genetic status in non-small cell cancer; however, the results have been conflicting and inconclusive. We analyzed the relationship between PD-L1 expression and clinicopathological f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 42 publications
6
26
0
Order By: Relevance
“…In the current study, we found that PD-L1 expression was associated with a higher N stage, which is consistent with one report of 1000 resected lung cancers in Korea which showed that PD-L1 expression in adenocarcinoma was associated with a higher N stage, solid histologic pattern, EGFR wild type, and ALK mutation [ 26 ]. Interestingly, PD-L1 expression was associated with M0 rather than M1 stage ( p = 0.049), and a similar trend was found in our series.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the current study, we found that PD-L1 expression was associated with a higher N stage, which is consistent with one report of 1000 resected lung cancers in Korea which showed that PD-L1 expression in adenocarcinoma was associated with a higher N stage, solid histologic pattern, EGFR wild type, and ALK mutation [ 26 ]. Interestingly, PD-L1 expression was associated with M0 rather than M1 stage ( p = 0.049), and a similar trend was found in our series.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, locally advanced lung cancer (higher N stage, M0, stage III) may have higher changes in PD-L1 expression than metastatic lung cancer (M1 stage, stage IV); however, the mechanism of tumor biology is unclear. In terms of genetic alterations, PD-L1 expression was associated with EGFR wild type and ALK mutations [ 26 , 27 ]. Similar trends were found in our series but did not reach statistical significance as limited cases are included in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have confirmed that PD‐L1 expression was associated with EGFR status 35,48,69–73 . Patients with EGFR mutations had decreased PD‐L1 expression according to a pool‐analysis of 15 public studies 28 .…”
Section: Immune Escape Mechanisms In Squamous and Adenocarcinoma Nsclcmentioning
confidence: 95%
“…While Shinchi Y et al 34 only detected a positive PD‐L1 expression rate of 26.8% in adenocarcinoma NSCLC. Two retrospective analyses also indicated a higher percentage of PD‐L1 expression in squamous than adenocarcinoma NSCLC (72.3% vs. 36.9% and 34.3% vs. 4.1%, respectively) 35,36 . The SP142 PD‐L1 IHC assay (Ventana) detected that the prevalence of PD‐L1 expression ranged from 50% to 55% in squamous NSCLC, 15,25,37–39 but was almost less than 40% in adenocarcinoma NSCLC 16,25,39 .…”
Section: Immune Escape Mechanisms In Squamous and Adenocarcinoma Nsclcmentioning
confidence: 97%
“…PD-L1 expression is recognized as a predictor of the ICI effect, and the TPS of PD-L1 of ≥50% in NSCLC has been reported to be 23.2% [ 10 ]. PD-L1 expression was significantly higher in patients with wild-type EGFR than those with EGFR mutations [ 11 ]. Cardona et al reported that 81.7% of patients with EGFR exon 20 insertions had TPS of PD-L1 of ≥1% expression [ 12 ].…”
Section: Discussionmentioning
confidence: 99%